2007
DOI: 10.1038/sj.mt.6300041
|View full text |Cite
|
Sign up to set email alerts
|

Intravenously Injected Human Fibroblasts Home to Skin Wounds, Deliver Type VII Collagen, and Promote Wound Healing

Abstract: Patients with dystrophic epidermolysis bullosa (DEB) have incurable skin fragility, blistering, and multiple skin wounds because of mutations in the gene that encodes for type VII collagen (C7), which holds together the epidermal and dermal layers of human skin. The intradermal injection of gene-corrected DEB fibroblasts, recombinant C7 protein, or lentiviral vectors expressing C7 is a potential therapy for DEB. Nevertheless, severe DEB causes widespread wounds and treatment would require multiple injections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 33 publications
2
66
0
3
Order By: Relevance
“…Woodley et al (28) recently reported that i.v. injection of human fibroblasts induces systemic production of human collagen VII in immunodeficient mice; however, major ethical and safety problems remain in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Woodley et al (28) recently reported that i.v. injection of human fibroblasts induces systemic production of human collagen VII in immunodeficient mice; however, major ethical and safety problems remain in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct evidence that purified C7 alone promotes keratinocyte motility was lacking. Our recent studies showed that there was a dramatic enhancement of skin wound closure in both murine and human skin wounds when wild type C7 was delivered early to healing wounds (37). These data suggest that C7 may possess properties that enhance cell migration.…”
Section: Resultsmentioning
confidence: 91%
“…In previous studies we observed that the wounds of mice IV injected with gene-corrected RDEB fibroblasts overexpressing C7 demonstrated accelerated wound healing compared with control mice injected with uncorrected RDEB cells (37). Similarly, C7 delivered to the wound bed via intradermal or intravenous injection of the recombinant protein also promoted accelerated closure of skin wounds.…”
Section: Figure 9 Migration Of Human Keratinocytes On Various C7 Mutmentioning
confidence: 98%
“…A feared complication of RDEB is squamous cell carcinoma, which arises at an early age in trauma-prone skin areas (15,16). Although clinical observations suggest that wound closure is impaired in RDEB (19)(20)(21), no study thus far has addressed the role of COL7A1 in wound healing.…”
Section: Introductionmentioning
confidence: 99%